Influence of endothelial function and arterial stiffness on the behavior of cervicocephalic arterial dissections: An observational study - Lee, Seong-Joon; Lee, Jin Soo; Kim, Min; Park, So Young; Park, Ji Hyun; Park, Bumhee; Jung, Woo Sang; Choi, Jin Wook; Hong, Ji Man (Frontiers in Neurology, 2022)
Background: The mechanical and physiological properties of the arterial wall might affect the behavior of spontaneous cervicocephalic arterial dissections (CCAD). We aimed to determine the effects of endothelial function and arterial stiffness on the clinical characteristics and outcomes of CCAD using brachial flow-mediated dilation (FMD) and brachial-ankle pulse wave velocity (PWV). Methods: From a single-center database, we identified patients admitted from April 2011 to December 2021 with a diagnosis of CCAD who underwent both FMD and PWV. FMD was classified as normal and decreased according to institutional thresholds. PWV was categorized into tertiles. Comparative and multivariable analyses were performed to determine the effects of FMD and PWV values on major clinical outcomes. Results: A total of 146 patients (age: 47±11 years; men: 77.4%) were included. The main presentation was ischemic stroke in 76.7% of the patients, while 23.3% presented with headache or other symptoms. Healing of the dissection was observed in 55.8%. In multivariable analysis, Normal FMD levels (vs. decreased; adjusted OR: 4.52, 95% CI [1.95 –10.52]) were associated with spontaneous healing of the dissection. Highest PWV tertile (vs. lowest; adjusted OR: 17.05, 95% CI [3.07–94.82]) was associated with ischemic presentation. There was a higher ischemic stroke recurrence in the 3rd PWV tertile, and more frequent aneurysmal enlargement in the lowest PWV tertile, but their frequency was low, precluding multivariable analysis. Conclusion: In spontaneous CCAD, preserved endothelial function was associated with spontaneous arterial healing. Arterial stiffness is associated with ischemic presentation.